PEMBERDAYAAN ANGGOTA PIMPINAN CABANG ‘AISYIYAH (PCA) GAMPING DALAM PENGOLAHAN SAMPAH POPOK SEKALI PAKAI - Oktira Roka Aji; Ambar Pratiwi; Nurul Suwartiningsih (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Disposable diaper waste takes hundreds of years to decompose and cause environmental pollution if disposed of directly into landfills or rivers. Therefore, innovation in the processing of disposable diaper waste and increasing public awareness for the processing of disposable diaper waste at the household level are needed. The purpose of this community service is to provide counseling and training to members of the Aisyiyah Branch (PCA) Gamping, Yogyakarta in managing disposable diaper waste into planting media. This activity was attended by 15 people from the board and members of PCA Gamping as well as local community leaders. The result of this community service activity is that there is an increase in the knowledge and skills of participants in processing disposable diaper waste into planting media. Through this activity, it is hoped that it will be useful to help reduce environmental pollution due to disposable diaper waste.